(untitled) (Jurnal Bahasa, 2008)
This study describes the sociolinguistic phenomenon of the Malay language in the Cocos Islands, especially in the Home Island, which is located in the Indian Ocean and is outside the region of Malay world. The study is based on the qualitative approach and ,focuses on five aspects: the genealogy and histoty of the Malays who migrated to the Cocos Islands: the forms of address among the Malays; the lexical and terminological .forms of the Malay language used by the Malays in the Cocos Islands. Interviews with open-ended questions were constructed to elicit responses from the informants and participant, observations were also carried out, in order to obtain data. A total of 6() informants comprising of local Malays and white Australians were interviewed from 2nd - 10th May 2004 in the Home Island. A typology ,framework area of language diffusion was applied in this study.